The Study of Arabic Grammar in Ethiopia: The Case of two Contemporary Muslim Learned Men - Gori, Alessandro (Aethiopica, 2008)
The article deals with the contribution of two contemporary Muslim Ethiopian scholars (šayḫ ʿAbd al-Bāṣiṭ b. Muḥammad b. Ḥasan al-Mināsī and šayḫ Muḥammad Amīn b. ʿAbdallāh al-Iṯyubī al-Hararī al-Muḥammadī) to the study of Arabic grammar. The position of this subject in the curricula of traditional Islamic education in Ethiopia is shortly described from both a diachronic and a synchronic perspective. The biography of the two learned men is analyzed with a special emphasis on the different phases of their training and on the literary outcomes of their activity. Finally, the main handbooks used in the Islamic educational centres in Ethiopia are listed to give the reader a clear idea of the frame in which the aspiring šayḫ-s and their masters study and teach.